2020
DOI: 10.3390/nano10020359
|View full text |Cite
|
Sign up to set email alerts
|

Laser Fragmentation Synthesis of Colloidal Bismuth Ferrite Particles

Abstract: Laser fragmentation of colloidal submicron-sized bismuth ferrite particles was performed by irradiating a liquid jet to synthesize bismuth ferrite nanoparticles. This treatment achieved a size reduction from 450 nm to below 10 nm. A circular and an elliptical fluid jet were compared to control the energy distribution within the fluid jet and thereby the product size distribution and educt decomposition. The resulting colloids were analysed via UV-VIS, XRD and TEM. All methods were used to gain information on s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 34 publications
(38 reference statements)
2
35
0
Order By: Relevance
“…At 10 kHz, the laser (Rofin PowerLine E, Hamburg, Germany) delivered 8 ns pulses with a fluence of 16.7 J/cm 2 , and LAL was performed for 5 min. Analog to earlier studies [30,45,59], a liquid jet setup was used for laser post-processing (LPP) of the laser-generated YIG colloids with a concentration of 160 mg/L (Figure 7). The colloid was directed through a glass nozzle (60 mL/min), forming a liquid jet with a diameter of 1.3 mm, which was irradiated with either ns-or a ps-pulses at 80 kHz repetition rate (Coherent Avia 355-23, Santa Clara, CA, USA, or Edgewave PX400-3-GH, Würselen, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…At 10 kHz, the laser (Rofin PowerLine E, Hamburg, Germany) delivered 8 ns pulses with a fluence of 16.7 J/cm 2 , and LAL was performed for 5 min. Analog to earlier studies [30,45,59], a liquid jet setup was used for laser post-processing (LPP) of the laser-generated YIG colloids with a concentration of 160 mg/L (Figure 7). The colloid was directed through a glass nozzle (60 mL/min), forming a liquid jet with a diameter of 1.3 mm, which was irradiated with either ns-or a ps-pulses at 80 kHz repetition rate (Coherent Avia 355-23, Santa Clara, CA, USA, or Edgewave PX400-3-GH, Würselen, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…In comparison, since the ultrashort lasers have distinct fragmentation mechanisms compared to ns laser, it may not be the perfect choice for the amorphization of NPs. For example, Waag et al 204 showed the synthesis of ultrasmall amorphous NPs and multi-crystalline particles up to 200 nm by ps-laser fragmentation of CoFe 2 O 4 particles in water, and Siebeneicher et al 205 using ps-laser fragmentation of bismuth ferrite particles suggested that the large particles dominated the crystalline characteristics in the XRD pattern although small amorphous NPs occupied the observation in TEM images. Since pulse duration of ps locates between ns and fs, those investigations of ps-laser might be involved with part of photothermal processes leading to the melting processes during fragmentation.…”
Section: Laser-based Processing Of Colloidal Amorphous Metal Nanoparticlesmentioning
confidence: 99%
“…Their presence might be explained by the detachment of the bigger chunks of the Ni plate into the solution when ablation was first initiated. Nonetheless, during the process they were split into smaller pieces, which confirms that laser irradiation might be used for homogenization of the nanoparticle solutions, or breaking-down aged solutions in which the nanoparticles have already agglomerated [ 29 , 48 , 49 ].…”
Section: Resultsmentioning
confidence: 99%